Development and validation of a novel simultaneous equation and Q-absorbance ratio method for the quantitative estimation of atenolol and hydrochlorothiazide in combined tablet dosage forms: A green analytical chemistry approach - Ashok H. Akabari; Divya K. Solanki; Sagarkumar K. Patel; Palak Desai; Gamit Jainisha; Bhavesh Patel; Birenkumar N. Shah; Ketan V. Shah (Green Analytical Chemistry)
This study aims to develop and validate novel UV spectrophotometric methods for the simultaneous estimation of atenolol and hydrochlorothiazide in pharmaceutical dosage forms and bulk. The proposed methods are Simultaneous Equation and Q-Absorbance Ratio methods offer a cost-effective, eco-friendly alternative to chromatographic techniques. The λmax of atenolol and hydrochlorothiazide were identified at 224.00 nm and 234.00 nm, respectively, with an isoabsorptive point at 229.00 nm for the Q-Absorbance Ratio method. The validation followed ICH Q2 (R1) guidelines, demonstrating excellent linearity (R² > 0.99 for both drugs), accuracy (98.5 %–101.2 %), precision (%RSD < 2 %), and sensitivity (LOD: 1.61 µg/mL for atenolol, 0.78 µg/mL for hydrochlorothiazide). The developed methods were successfully applied to a marketed formulation, showing recovery rates within acceptable limits. The environmental sustainability of these methods was assessed using ComplexGAPI, AGREE, Analytical Eco-Scale, ChlorTox WHN, and CHEMS-1 tools. The AGREE score (0.71) and ComplexGAPI assessment (eight green attributes, two red) confirmed superior eco-friendliness over reported HPLC methods (AGREE: 0.62). ChlorTox scores further validated minimal toxicity risks. This research highlights an efficient, accurate, and environmentally benign alternative for atenolol and hydrochlorothiazide analysis, aligning with green analytical chemistry principles.